2y-3=3y

Simple and best practice solution for 2y-3=3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-3=3y equation:


Simplifying
2y + -3 = 3y

Reorder the terms:
-3 + 2y = 3y

Solving
-3 + 2y = 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-3 + 2y + -3y = 3y + -3y

Combine like terms: 2y + -3y = -1y
-3 + -1y = 3y + -3y

Combine like terms: 3y + -3y = 0
-3 + -1y = 0

Add '3' to each side of the equation.
-3 + 3 + -1y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -1y = 0 + 3
-1y = 0 + 3

Combine like terms: 0 + 3 = 3
-1y = 3

Divide each side by '-1'.
y = -3

Simplifying
y = -3

See similar equations:

| 2c^3+16c^2-18c=0 | | (x-3)=-2 | | 20x^3-20x=0 | | 4(6x+2)=56 | | 3x-4=4x-17 | | k^2-3k+5=0 | | 4y-7=2(y+1) | | F=1.8(37)+32 | | 5y-20=10 | | 12x^5+15x+9=0 | | -x^2+15x+54=0 | | K=10+273 | | 2x+6=-26-6x | | 4y-1=2y+2 | | X^2=3(5x+18) | | 5x+5-2x=29 | | 9+6x=x+59 | | (3x-2)(x-2)=4x-36 | | 20y-16=18-9 | | K=40+273 | | 4(3a-2)+3a=19 | | F=1.8(40)+32 | | 7x-10=114-6x | | 305=5x^3 | | K=30+273 | | -6+7x=x-12 | | 3(2x+5)=11-4x | | 6y(4y-3)+15y= | | 15x+5=80 | | 5-2(-3/5)=3(-3/5)+8 | | 4-2(x+5)=9 | | F=1.8(30)+32 |

Equations solver categories